Tuned mass-damper-inerter control of wind-induced vibration of flexible structures based on inerter location. (15th November 2019) - Dai, Jun; Xu, Zhao-Dong; Gai, Pan-Pan
Highlights: The effect of the inerter location on control performances of the TMDI is analyzed. The high-mode damping effect of the TMDI is explained using the control robustness. An empirical formula is proposed to estimate the optimum frequency of the TMDI. The TMDI is numerically used to mitigate the vortex-induced vibration of bridges. Abstract: This paper investigates the effect of inerter location on the control performance of the tuned mass-damper-inerter (TMDI) in the wind-induced vibration mitigation of flexible structures. First, the equation of motion for the structure-TMDI system considering the inerter location is established. Then, the changes of the control effect, optimum design parameters, and high-mode damping effect of the TMDI with the inerter location are discussed based on the negative stiffness effect, mass amplification effect, and control robustness. An empirical formula is proposed to estimate the optimum frequency of the TMDI with different inerter locations. At last, numerical simulations of a wind-excited benchmark building and a continuous steel box-girder bridge are performed to illustrate the feasibility and effectiveness of the TMDI. The numerical results show that the TMDI has better control performance when the inerter spans more floors or longer girder length. The control performance of the TMDI is superior to that of the conventional tuned mass damper if the end of inerter is located in the position with a relatively small controlled mode value, which depends on the mass and inertance of the TMDI. Increasing the inertance of the inerter can effectively improve the high-mode damping effect of the TMDI, and optimizing the inerter location is more efficient for the fundamental mode vibration mitigation.